Struggle For Women's Rights In Danielle Steel's Answered Prayers: Feminist Approach - Herlina, Safitri Agustin (2004)
The major problem of this study is to reveal how the major character struggles for women's rights. The objective of this study is to analyze the novel based on its structural elements and to analyze the novel based on the feminist analysis. In analyzing Answered Prayers, the writer uses qualitative method and feminist approach. The object of the study is Danielle Steel's Answered Prayers published in 2003 by Bantam dell. The data sources are primary data and secondary data sources. The primary data source is the novel Answered Prayers itself and the secondary data sources are the other sources related to the analysis such as the author's biography, books of literary theory and feminism, especially feminism history in America. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of the study shows in the following conclusion. First, in this novel, Danielle Steel wants to illustrate how women are subordinate in Patriarchal Society. Second, in this novel, Danielle Steel wants to say that women's rights are not given but must be struggled for. The last, in this novel, Danielle Steel wants to assert that in order to get their rights, women should rebel against patriarchal society in the issue of women's position, role, participation and rights